Should Jesus Christ Be at the Centre of Introductions to Christian Ethics?. (February 2020) - Townsend, Nicholas
Prima facie, Christian ethics will be centred on Jesus Christ, but to what extent can and should textbooks for academic study of the field have this focus? Perhaps the two most influential Anglophone Christian ethicists of recent decades are Stanley Hauerwas and Oliver O'Donovan. Their introductory (if demanding) volumes ( The Peaceable Kingdom, 1983, and Resurrection and Moral Order, 1986) were both very Christocentric although in different ways. Yet recent textbooks in the discipline generally do not manifest such a strong focus on Jesus Christ. This generates one criterion by which we might assess such books. This article reviews six textbooks, four by UK and two by US authors. It suggests that other criteria for assessment include whether they give appropriate prominence to the Pauline vision of 'life by the Spirit', whether they manifest such pastoral responsibility as Christian ethicists have for students, and whether they are alert to overlapping concerns in Christian ethics and missiology.